Summer 1995 report from Jane R. Clark - Clark, Janeet al (1995)
An annotated list of birds sighted by Jane Clark and others. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of summer 1995. Epson - sheet feed/flatbed